Genetic parameters of subjective and image-based horn fly abundance phenotypes - Warner, Amanda M.; Heins, Bradley D.; Hinkle, Nancy C.; Pringle, Timothy D.; Aggrey, Samuel E.; Rekaya, Romdhane (Frontiers in Animal Science, 2023)
The genetic basis of horn fly abundance remains largely unknown and only few heritability estimates are available based on small scale studies. In this study, one subjective and two image-based fly abundance phenotypes were analyzed. Each animal was assessed subjectively for fly abundance by at least one trained agent (SUB). Additionally, several digital images were taken and the best image for each animal was used to assess fly abundance. A box that runs roughly from the withers to the hook and from the chest floor to the fore of the udder was established and all horn flies (PA) and samplingbased estimated number of flies (PR) within the box were calculated. Horn fly counts (SUB, PA, and PR) were discretized into 4 classes based on the quartiles of their respective distributions. Heritability estimates ranged between 0.10 and 0.15 and between 0.14 and 0.16 for the continuous and discrete cases, respectively. The genetic correlation was 0.66 between PA and PR and decreased significantly between the image-based (PA and PR) and the subjective (SUB) assessments for the continuous case. For the discrete case, the genetic correlations between the three traits were very similar, indicating a high concordance between traits.